Imagined pet touch versus non-tactile presence: A within-person experimental study of emotional support during stress - Brian N. Chin; Cat S. Crocker; Noah M. McEachern (Human-Animal Interactions)
Abstract This study tested whether affectionate touch enhances the emotional benefits of pet-based support during stress. In a within-person experiment conducted in April 2025, 196 US cat and dog owners imagined receiving support from their pet in two scenarios during a guided visualization task. In both conditions, participants visualized the same stressful life event; one scenario involved imagined pet presence without touch, and the other involved imagined physical contact. After each vignette, participants rated their perceived stress, emotional comfort, and positive affect. Imagined pet touch was associated with lower perceived stress and greater emotional comfort and positive affect compared to pet presence alone. Exploratory moderation analyses showed that pet attachment avoidance moderated these effects: participants high in avoidance did not report increased comfort or positive affect in response to imagined touch. This suggests that human-animal relationship security may shape receptivity to emotionally supportive interactions with pets. These results were consistent across participants who visualized a cat or a dog. These findings provide experimental evidence that affectionate touch, even when imagined, may represent a key psychological mechanism through which people experience pet-related emotional support. They also highlight the role of individual differences in attachment in shaping the emotional impact of pet-based support. Future research should isolate and compare additional mechanisms – such as gaze, proximity, or shared routines – to develop a more precise model of how companion animals support emotion regulation and inform more targeted approaches in animal-assisted interventions.